Novel form of miR-29b suppresses bleomycin-induced pulmonary fibrosis. - Yuko Yamada; Masakatsu Takanashi; Katsuko Sudo; Shinobu Ueda; Shin-Ichiro Ohno; Masahiko Kuroda (PLoS ONE, 2017)
MicroRNA 29b (miR-29b) replacement therapy is effective for suppressing fibrosis in a mouse model. However, to develop clinical applications for miRNA mimics, the side effects of nucleic acid drugs have to be addressed. In this study, we focused on miRNA mimics in order to develop therapies for idiopathic pulmonary fibrosis. We developed a single-stranded RNA, termed "miR-29b Psh-match," that has a unique structure to avoid problems associated with the therapeutic uses of miRNAs. A comparison of miR-29b Psh-match and double-stranded one, termed "miR-29b mimic" indicated that the single-stranded form was significantly effective towards fibrosis according to both in vivo and in vitro experiments. This novel form of miR-29b may become the foundation for developing an effective therapeutic drug for pulmonary fibrosis.